2009
DOI: 10.4022/jafib.v1i7.539
|View full text |Cite
|
Sign up to set email alerts
|

The Phrenic Nerve and Atrial Fibrillation Ablation Procedures

Abstract: Radiofrequency ablation is increasingly used as an option to optimally manage patients with symptomatic atrial fibrillation. Presently, ablationists strive to improve success rates, particularly with persistent atrial fibrillation, while simultaneously attempting to reduce complications. A well-recognized complication with atrial fibrillation ablation is injury to the phrenic nerve giving rise to diaphragmatic paresis and patient discomfort.Phrenic nerve damage may occur when performing common components of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Therefore rigorous monitoring of phrenic nerve capture and early detection of changes to CMAP remains the cornerstone to mitigate the risk of PNI. A decrease in the CMAP amplitude is the earliest sign of detectable injury to the phrenic nerve, 18 and is easy to measure. Therefore, close monitoring is required from the start of RF delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore rigorous monitoring of phrenic nerve capture and early detection of changes to CMAP remains the cornerstone to mitigate the risk of PNI. A decrease in the CMAP amplitude is the earliest sign of detectable injury to the phrenic nerve, 18 and is easy to measure. Therefore, close monitoring is required from the start of RF delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complication involves injury to the right phrenic nerve, which courses in close proximity to the SVC. 4 Injury is typically observed during ablation of the posterolateral SVC. Although injury results in paralysis of the right hemidiaphragm, most patients will recover within a year.…”
Section: Discussionmentioning
confidence: 99%
“…Phrenic nerve palsy is another complication of PVI by using thermal ablation. [19] In 2015, van Driel et al [31] found no evidence of right phrenic nerve damage after intentionally targeted ablation using circular 200-J DC applications with good tissue contact inside the superior vena cava wall. Occasionally, transient nerve palsy was induced, but normal pacing was monitored from the superior vena cava 30 minutes and 3 to 13 weeks after ablation.…”
Section: No Evidence Of Phrenic Nerve Damagementioning
confidence: 99%
“…The phrenic nerves are located very close to the superior vena cava, right PVs, and LA appendage. Phrenic nerve palsy is another complication of PVI by using thermal ablation [19] . In 2015, van Driel et al [31] found no evidence of right phrenic nerve damage after intentionally targeted ablation using circular 200-J DC applications with good tissue contact inside the superior vena cava wall.…”
Section: History Of Irreversible Electroporation (Ire) and Its Applic...mentioning
confidence: 99%
See 1 more Smart Citation